2022
DOI: 10.1371/journal.pntd.0009524
|View full text |Cite|
|
Sign up to set email alerts
|

Opportunity or catastrophe? effect of sea salt on host-parasite survival and reproduction

Abstract: Seawater intrusion associated with decreasing groundwater levels and rising seawater levels may affect freshwater species and their parasites. While brackish water certainly impacts freshwater systems globally, its impact on disease transmission is largely unknown. This study examined the effect of artificial seawater on host-parasite interactions using a freshwater snail host, Biomphalaria alexandrina, and the human trematode parasite Schistosoma mansoni. To evaluate the impact of increasing salinity on disea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…These snails are an essential part of the parasite's life cycle, and their presence is necessary for the successful transmission of schistosomiasis. Factors which influence hatching include temperature, light and salinity and freshwater provides the right environment for the eggs to hatch into the miracidium as well as for the miracidium to survive in the water [ 110 ].Studies have shown that water with high salt content is deadly to miracidia [ 109 , 111 , 112 ].…”
Section: Transmission and Life Cycle Of Schistosomesmentioning
confidence: 99%
“…These snails are an essential part of the parasite's life cycle, and their presence is necessary for the successful transmission of schistosomiasis. Factors which influence hatching include temperature, light and salinity and freshwater provides the right environment for the eggs to hatch into the miracidium as well as for the miracidium to survive in the water [ 110 ].Studies have shown that water with high salt content is deadly to miracidia [ 109 , 111 , 112 ].…”
Section: Transmission and Life Cycle Of Schistosomesmentioning
confidence: 99%